LOCAL MIXED COMPANIES: THE THEORY AND PRACTICE IN AN INTERNATIONAL PERSPECTIVE. (March 2014) - CRUZ, N.F.; MARQUES, R.C.; MARRA, A.; POZZI, C.; Marra, A.; Cruz, N.F.; Fecher, F.; Marques, R.C.
ABSTRACT Several factors have been contributing to the growing use of public private‐partnership (PPP) arrangements by local governments, such as, the need for new investments on infrastructure (e.g. decentralization of responsibilities, regulatory requirements demanding better quality and environmental protection, renovation of the networks), imposition of strict debt limits to the localities, and local government reform policies/programs. Whereas contractual PPP arrangements, such as concession contracts, can be seen as an extension of traditional public procurement (with additional complexities in contract design and management) and are currently better handled by contracting authorities, institutionalized PPPs (mixed companies) are still quite puzzling for both practitioners and academics. In fact, the following questions deserve further investigation: When are mixed companies expected to depict a higher performance than other options? What are the risks involved and how should they be allocated and mitigated? How should mixed companies be monitored and evaluated? The articles in this Special Issue provide insightful answers to these and many other relevant questions to policy makers.